2016
DOI: 10.1016/j.powtec.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a dimensional analysis of spheronisation of cylindrical extrudates

Abstract: Extrusion-spheronisation (E-S) is a widely used technique for the manufacture of pellets with high sphericity and narrow size distribution. A dimensionless framework for describing the evolution of pellet shape with spheronisation time is presented.The experiments employed a 45 wt% microcrystalline cellulose (MCC)/water-based paste, with up to 15 wt% calcium carbonate added to represent a 'hard' active pharmaceutical ingredient (API). The bulk yield strength of the paste was measured and found to increase with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Lau et al 6 interpreted this finding in terms of the number of revolutions of the plate and thus number of collisions, which pellets experience. Parkin et al 7 measured pellet velocities in spheronization tests similar to those reported here and found that the rotational speeds were smaller than Rω, but this value provided an upper limit to the range observed. Since the energy in collisions will scale with kinetic energy, and thus (Rω) 2 , and the number of collisions is likely to relate to the number of revolutions (ωt s ), Lau et al postulated that the work required to round a pellet would be proportional to R 2 ω 3 t s .…”
Section: Introductionsupporting
confidence: 73%
“…Lau et al 6 interpreted this finding in terms of the number of revolutions of the plate and thus number of collisions, which pellets experience. Parkin et al 7 measured pellet velocities in spheronization tests similar to those reported here and found that the rotational speeds were smaller than Rω, but this value provided an upper limit to the range observed. Since the energy in collisions will scale with kinetic energy, and thus (Rω) 2 , and the number of collisions is likely to relate to the number of revolutions (ωt s ), Lau et al postulated that the work required to round a pellet would be proportional to R 2 ω 3 t s .…”
Section: Introductionsupporting
confidence: 73%
“…Video analyses (e.g. [20]) confirmed that pellet velocities were of order R, and usually significantly below this value. 4 By comparison, there is little in the published literature on screen extrudate-spheroniser interactions and their effect on pellet quality.…”
Section: Influence Of the Spheronisation Platementioning
confidence: 92%
“…There is no consistent trend for plates with θ  45 o : plates A, B and E give relatively even surfaces for D  2 mm, whereas pellets generated using C and F from similar extrudates were dimpled. 20 Visual inspection suggests that pellets with D/d* > 1.5 tended to be smoother: in this case, the pellet bed would be more likely to roll over the plate, promoting collisions from many contacts and thus rounding. More energetic collisions are expected to result in dents and cracks.…”
Section: Pellet Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our research, we can obtain the dimensional matrix according to dimensionless variables. Dimensional matrix consists of two parts: Kernel matrix and residual matrix . The physical variables are first lined up, and the basic dimensions are arranged in a row.…”
Section: The Kinetic Mathematical Modelmentioning
confidence: 99%